Soil water surplus and ENSO events during the last humid period in Argentine Pampean flatlands - Scarpati, Olga Eugenia (2009)
Daily soil water balances are estimated for the period 1951-2006 in the Pampean flatlands. Daily soil water surplus is the major output with their annual trends, being analysed because of their harmful effects on crop harvests and floods. Soil water surplus trends were analysed founding positive trends, although only two stations were statistically significant at probability level of 95%. Differing phases of ENSO – using the multivariate ENSO index (MEI) – have differing impacts on rain and soil moisture conditions. The probabilities of occurrence of predetermined soil water surplus and hence flood risk are calculated and mapped.